Prevalence and Risk Factors of Mastitis among Dairy Buffaloes from the Departments of Antioquia and Córdoba, Colombia - García-Acevedo, Jhon F.; Tobón, Julián D.; Grisales, Camilo F.; Gómez, Catalina; Fernández-Silva, Jorge A.; Ramírez-Vásquez, Nicolás F. (Journal of Buffalo Science, 2023)
Background: Mastitis is the most common disease among dairy buffaloes worldwide, and it significantly affects the economic profitability of buffalo farms as well as animal welfare and public health. Methods: This study was conducted between 2018 and 2019 at the Colombian departments of Antioquia and Córdoba, where 41% of the country’s total buffalo population is concentrated. Overall, 1,018 dairy buffaloes, including 603 in Antioquia and 415 in Córdoba, distributed among 11 farms, were assessed in the study. These animals were evaluated using the California mastitis test (CMT) and somatic cell count (SCC) to determine the presence of subclinical mastitis (SM). They were considered positive for SM when the results of CMT were higher than traces and SCC was >200,000 cells/mL. Results: The total prevalence of the disease was 7.9%, and microbiological culture was performed on the samples obtained from the SM-positive animals. The main isolated bacterium was coagulase-negative Staphylococcus. Furthermore, risk factors affecting milking routine, hygiene, and farm facilities were determined. Manual milking, milking in the barn, non-disinfection of milkers' hands, etc., were identified as risk factors for the disease. Conclusion: To the best of our knowledge, this is the first large-scale study of mastitis among buffaloes in Colombia.